Defending a New Domain: The Pentagon's Cyberstrategy. - Lynn, William J. (Foreign Affairs)
At the moment, over 100 foreign intelligence organizations are attempting to hack into the digital networks that underpin all operations of the U.S. military. The Pentagon recognizes the disastrous threat that cyberwarfare poses to the country's national security. For this reason, it has established partnerships with allied governments and private firms, invented high-tech cyberdefenses, and set up the new Cyber Command in the U.S. military.